Vaginal ligation of descending branch of uterine artery in the management of massive secondary post-partum haemorrhage - Chandra, Rudrika; Singh, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
A 25 year old lady presented on day 22 of an uneventful caesarean delivery, in a state of class IV haemorrhagic shock, secondary to sudden onset of vaginal bleeding without any inciting cause. Immediate resuscitation was initiated and the cause for massive secondary post-partum haemorrhage (PPH) was identified as an actively bleeding vessel at 3 ‘O’ clock position on a visibly healthy cervix with a well contracted uterus. This was the descending branch of left uterine artery, which was ligated after pulling the cervix with a sponge holder towards the introitus and application of Vicryl No 1-0 suture. The bleeding decreased significantly post vascular ligation. Further exploration of vagina and cervix did not reveal any active bleeding or laceration and no retained placental tissue was found inside uterine cavity on ultrasound examination. This is a rare case of Massive Secondary PPH in a post-caesarean patient due to spontaneous giving way of descending branch of uterine artery.